The Evaluation of Serum KIM-1 in a Pediatric Cohort of Renal Transplantation—A Pilot Study - Paul Luchian Aldea; Roxana Andreea Turbuleasa-Jurje; Bogdan Bulata; Dan Delean; Florin Ioan Elec; Lorena Ciumarnean; Andreea Liana Bot (Rachisan) (Children)
Introduction: Renal transplantation ensures particular advantages for patients with end-stage kidney disease. However, in some cases, early complications may result in allograft dysfunction, which can ultimately lead to the loss of the graft. Creatinine is a poor biomarker for kidney injury due principally to its inability to help diagnose early acute renal failure and complete inability to help differentiate among its various causes. Different urinary and serum proteins have been intensively investigated as possible biomarkers in this setting. We focused on emerging serum biomarkers such as kidney injury molecule 1 (KIM-1) on a cohort of grafted patients. The motivation of this study was to analyze a predictive biological marker in comparison with standard markers for the evaluation of renal function, with the aim of observing if there are statistically significant differences regarding the performance and promptness of its increase compared to the current monitoring methods in order to improve graft survival, quality of life, and overall patient prognosis. Patients and Methods: We included 21 patients who had their first kidney transplantation (8 females, 13 males), with a follow-up period from transplantation of 3.14 years, without prior immunization, having complete HLA typing and a negative cross-match test before transplantation. We determined serum creatinine and KIM-1 in the whole cohort at the time of the enrollment in the study. Results: The mean creatinine value was 0.89 mg/dL ± 0.33. The mean value for KIM-1 was 13.56 +/− 21.52 in the Tx group vs. 5.91 +/− 3.26 in the control group with a p-value of 0.06. We defined patients at low risk (LR) of graft loss (serum creatinine < 0.9 mg/dL) and those at high risk (HR) (serum creatinine > 0.91 mg/dL). The mean values for KIM-1 were 6.09 +/− 1.67 in the LR vs. 21.77 +/− 29.71 in the HR group, with a p-value 0.01. Conclusions: There is a strong difference for KIM-1 at 24 h postTx between the two groups, showing a high correlation between KIM-1 and the predisposition of the graft dysfunction. Further studies are needed in order to clarify the utility of these novel biomarkers in the prediction of graft survival in renal transplantation patients.